Extraction Yields and Anti‐oxidant Activity of Proanthocyanidins from Different Parts of Grape Pomace: Effect of Mechanical Treatments. Issue 2 (3rd October 2013) - de, M.; Justino, V.; Spranger, M. I.; Zhao, Y. Q.; Han, L.; Sun, B. S.
ABSTRACT Introduction White grape pomace is not subject to maceration, keeping nearly all polyphenols of grapes, so they represent important sources of bioactive compounds such as proanthocyanidins. Preparation of plant polyphenol extracts is usually performed using raw material powder. However, the fine particles make the further extraction procedure steps more difficult. Objective To study the effect of mechanical treatments on extraction yields and anti‐oxidant activity from different parts of white grape pomace. Methods Skins, stems and seeds were isolated from the pomace of white winemaking process. Sequential solvent extraction of polyphenols, first using 80% methanol in water followed by 75% acetone in water, was carried out on both entire and milled (< 1 mm) grape solids; extraction on seed polyphenols was also performed in its squashed form. The phenolic content of each extract was verified by spectrometric and HPLC methods and its anti‐oxidant activity was evaluated by the 1, 1‐diphenyl‐2‐picrylhydrazyl test. Results More total polyphenols can be extracted from each milled tissue than from its entire form. Seeds present the highest total phenol, oligomeric and polymeric proanthocyanidin content, and similar extraction yield was found between milled and squashed tissues. The HPLC analysis showed no difference in extraction yield of low‐molecular‐weight proanthocyanidins between milled and entire stems. Anti‐oxidant activity showed a positive correlation with total phenol content, galloyled oligomers and polymeric proanthocyanidins. Conclusion The use of entire stems and squashed seeds for solvent extraction of polyphenols makes manipulation simpler and more cost‐efficient, providing similar extraction yields to using their powdery forms. Copyright © 2013 John Wiley & Sons, Ltd.